1967
DOI: 10.2136/sssaj1967.03615995003100060026x
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Chemical Characteristics of Soils in Loess Overlying Shale in Northwestern Illinois

Abstract: Eleroy and Derinda soils (Typic Hapludalfs) and Keltner and Schapville soils (Typic Argiudolls) were studied. Weathering of silt‐size minerals is not advanced in these relatively youthful soils. Iron is the most sensitive indicator of weathering, being particularly labile in the Hapludalf profiles. Iron weathers from silt‐size minerals and is localized in concretions and in the clay fraction. Clay‐mineral weathering involves formation of chloritized vermiculite and montmorillonite from illite and montmorilloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The somewhat greater vermiculite content in the loess of the Green Bay Lobe relative to the Driftless Area may be due to the weathering of the thinner loess mantle. Oxidation and weathering of detrital chlorite to vermiculite and possibly transformation of mica to vermiculite have been documented in thin loess mantles, although the latter reaction is mostly restricted to upper horizons of soils such as these (Jones et al, 1967;Borchert et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…The somewhat greater vermiculite content in the loess of the Green Bay Lobe relative to the Driftless Area may be due to the weathering of the thinner loess mantle. Oxidation and weathering of detrital chlorite to vermiculite and possibly transformation of mica to vermiculite have been documented in thin loess mantles, although the latter reaction is mostly restricted to upper horizons of soils such as these (Jones et al, 1967;Borchert et al, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Pioneering work on the geochemistry of loess by workers in Illinois identified silt-size fractions where certain elements are concentrated. Beavers et al (1963) and Jones et al (1967) found that Zr has the highest concentrations in coarse silt (50-20 pm), whereas Ti and K have the highest concentrations in fine silt (20-2 pm), when size fractions are separated by sedimentation. Therefore, it is expected that Zr concentrations ought to decrease away from a source whereas K and Ti concentrations should increase away from a source.…”
Section: Upper Peoria Loess Transect In Western Iowamentioning
confidence: 99%
“…The loess-derived soils are very productive due to their ability to hold water and nutrients (Jones et al, 1967). However, the fields in Clear Creek have some of the highest erosion rates in Iowa (e.g., Cruse et al, 2006).…”
Section: Soilsmentioning
confidence: 99%